Implementasi Metode Benchmarking dalam Peningkatan Mutu Pendidikan: Lesson Learned dari Studi Komparasi - Lailatussaadah; Nurmayuli; Raihana , Zaitun (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
The quality of schools reflects the quality of education, the learning process, and the learning environment in those schools. With the rapid advancement of the times, the process of enhancing these aspects is increasingly developing; this quality becomes one of the aspects of competition in the world of education. The aim of this study is to discover the lesson learned from the benchmarking method in improving the quality of education at MTsN 1 Model Banda Aceh. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The subjects in this study were determined using purposive sampling and snowball sampling, involving the Deputy Head of the Madrasah for Public Relations, the Deputy Head of the Madrasah for Student Affairs, and 8 teachers. The research was conducted at MTsN 1 Model Banda Aceh. The research findings reveal lessons learned from the benchmarking method, which pertains to the curriculum standards including tahfidz programs and robotics programs, as well as infrastructure standards covering fingerprint systems and herbal gardens. The implementation process is still in the execution stage concerning curriculum standards and infrastructure at MTsN 1 Model Banda Aceh. The implications of the benchmarking method include gaining positive experiences, broadening perspectives, and fostering new innovations concerning the quality of education at the visited educational institution.